In a suit of fire: Memory, gender and resistance - Montero Jiménez , Marian (2025)
In a Suit of Fire: Memory, Gender, and Resistance, written by Francisco Rodríguez Cascante and directed by Carlos Paniagua, is a theatrical work that revives the figure of Costa Rican intellectual Corina Rodríguez López. Combining biography and poetry, the play explores the intimate, political, and symbolic dimensions of her life, marked by her fight against patriarchy and her defense of education and free thought. Through scenes that alternate between reflective old age and memories of childhood and youth, the dramaturgy portrays a woman who transformed words and teaching into acts of resistance. The “fire” in the title represents passion, memory, and sacrifice, elements that define Corina’s journey and symbolize the transformative power of art. The play becomes both a tribute to women who defy silence and a reflection on freedom, dignity, and ethical coherence. Beyond the individual portrait, In a Suit of Fire is a meditation on collective memory and on theatre’s role as a space for symbolic representation.